Strengthening of weak masonry assemblages using wire reinforced cementitious matrix (WRCM) for shear and flexure loads. (29th March 2021) - Tripathy, D.; Singhal, V.
Highlights: Effectiveness of WRCM for strengthening of low-strength masonry assemblages. Series of tests done to assess flexure and shear response of small-size specimens. Properties of matrix play a vital role in the performance of strengthened masonry. Study suggest to use suitable type of wire mesh and anchor for better performance. Abstract: The wire reinforced cementitious matrix (WRCM) was used to improve the in-plane and out-of-plane performance of weak masonry assemblages. Six different types of WRCMs were used to strengthen small-size masonry assemblages and to understand the role of various parameters such as tensile strength of welded wire mesh, compressive strength of masonry and cementitious matrix in influencing the efficiency of the strengthening scheme. An experimental program consisting of diagonal compression and four-point bending test was conducted to evaluate the in-plane (shear) and out-of-plane (flexural) strength of strengthened masonry assemblages. Two types of low-strength mortar; 1:6 cement-sand, and mud mortar was used to prepare the masonry specimens. A total of 120 specimens with 40 specimens each for the diagonal compression test and flexure test with failure plane-parallel and perpendicular to the bed joint were prepared and tested under quasi-static displacement control loading. Test results showed that the WRCM strengthening scheme is effective and can significantly enhance the shear, and flexural strength and ductility of low-strength masonry assemblages. This study illustrates that the strength of cementitious matrix can also play an important role in contributing to the flexural and shear behavior of the WRCM strengthened masonry. Further, the experimental results were compared with theoretical predictions estimated using the available analytical models.